Pause now handbook for a spiritual revolution - Yastion, Lyla. (Lanham, Md. : Hamilton Books, 2009)
This handbook in practical spirituality proposes that the level of stress, violence, fear and disconnect from Nature in the global society has risen in direct proportion to a fall in the collective level of conscious awareness. In order to reverse this trend a conscious impulse is required. Human beings need to rediscover the mystical underpinning of all religions and the engine of spiritual transformation: the art of presence. Only by learning to be present and stay present is it possible to dissolve harmful energy - in the form of false opinions and negative feelings - and create positive en
List of Illustrations; Acknowledgments; Introduction; Chapter 01. The Secret; Chapter 02. A Spirituality of the Senses: The Pause; Chapter 03. The Steps: a close-up: Posture and the Spirituality of Touch; Chapter 04. Close-up continued: The Spiritualities of Seeing, Smelling and Tasting; Chapter 05. Close-up Concluded: The Spirituality of Listening; Resting in Simple Awareness; Chapter 06. The Spirituality of Moving; Chapter 07. The Spirituality of Speaking; Chapter 08. The Spiritualities of Work and Play; Chapter 09. The Spirituality of Thinking
Includes bibliographical references and index.
Description based on print version record.
Keywords: Spiritual life -- Handbooks, manuals, etc; Spirituality -- Handbooks, manuals, etc; Conduct of life -- Handbooks, manuals, etc; Awareness -- Religious aspects -- Handbooks, manuals, etc; RELIGION -- Inspirational; SELF-HELP -- Spiritual; Electronic books